ANALISIS PENGARUH DANA PERIMBANGAN DAN BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI SULAWESI TENGGARA TAHUN 2004-2014 - Rahmah Saim; Syamsul Anam (JEP (Jurnal Ekonomi Pembangunan), 2016)
This study aims to analyze effect of the development of regional balance and spending funds on economic growth in Southeast Sulawesi Province. The data used are secondary data for the 2004-2014. The data analysis is used multiple linear regression. The results of this study indicate that the development of the allocation of balanced funds and regional spending has increased. Balance funds which include general allocation funds and revenue sharing funds. General allocation funds have a significant effect on economic growth, while revenue-sharing funds not significant on economic growth. The other side, the effect ofÂ  regional expenditure on economic growth not significant.